Impacto da vacinação contra influenza no perfil de mortalidade de idosos no Brasil - Suares, Andresa da Cunha (2017)
Respiratory diseases, including influenza virus infection and its complications are major causes of mortality particularly in the elderly. Influenza vaccination has emerged as a national strategy to reduce the impact on mortality from respiratory diseases in the elderly and has been managed since 1999. This study aimed to evaluate the impact of influenza vaccination on the mortality trend from respiratory diseases in the Brazilian elderly population (≥ 60 years), in the period from 2008 to 2014. Deaths from respiratory diseases associated with influenza were analyzed according to gender and age and compared to vaccination coverage against influenza in the study population. This observational, longitudinal mixed-type ecological study combined different time periods and territories in different age groups. Secondary data from the Mortality Information System of the Ministry of Health (SIM / MS), National Immunization Program Information System (NIP-SI) and estimates from the Brazilian Institute of Geography and Statistics (IBGE) were used. Mortality rates for selected causes were related with the age of the study population. Moreover, higher mortality rates were observed among men and among residents in the South and Southeast regions of Brazil. Mortality coefficients did not show a significant increase in the year 2009 when the first pandemic of the 21st century occurred due to Pandemic Influenza (H1N1). Mortality rates from respiratory diseases and influenza vaccination coverage were not correlated. The present study assessed the impact of influenza vaccination on mortality rates of elderly people nationwide through a historical data series. However the seasonality of influenza virus must be considered in order to determine preventive actions and guide local public health policies.